Sciences participatives et biodiversité : de l’exploration à la transformation des socio-écosystèmes - Denis Couvet; Anne Teyssèdre (Cahiers des Amériques Latines)
Participatory sciences contribute significantly to the progress of research on the environment and biodiversity. They can be distinguished according to their objective, revealing complementary logic. «Exploratory» researches, which objective is to produce knowledge, are generally initiated and driven by research laboratories. «Transformative» researches have as direct objective ecosystem management and/or biodiversity conservation, and are often initiated and conducted by practitioners or «stakeholders» (NGOs, local authorities…). In this paper we explore the logical problems, but also the complementarities and possible evolution of these two types of participatory research.